2016
DOI: 10.1002/2016gl069653
|View full text |Cite
|
Sign up to set email alerts
|

A new perspective on global mean sea level (GMSL) acceleration

Abstract: The vast body of contemporary climate change science is largely underpinned by the premise of a measured acceleration from anthropogenic forcings evident in key climate change proxies—greenhouse gas emissions, temperature, and mean sea level. By virtue, over recent years, the issue of whether or not there is a measurable acceleration in global mean sea level has resulted in fierce, widespread professional, social, and political debate. Attempts to measure acceleration in global mean sea level (GMSL) have often… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…85,86 However, the significance of that acceleration (in the tide gauge data at least) depends on the analysis method, some analyses finding that the evidence for acceleration is less persuasive than others. [87][88][89] (See discussion of methods for determining acceleration in Refs. 90-92.…”
Section: Twentieth-twenty First Century Msl Rise and Accelerationmentioning
confidence: 99%
See 1 more Smart Citation
“…85,86 However, the significance of that acceleration (in the tide gauge data at least) depends on the analysis method, some analyses finding that the evidence for acceleration is less persuasive than others. [87][88][89] (See discussion of methods for determining acceleration in Refs. 90-92.…”
Section: Twentieth-twenty First Century Msl Rise and Accelerationmentioning
confidence: 99%
“…The SROCC and AR6 findings show that there is never a linear rate of sea level rise, but at times, the rate is accelerating or decelerating. For example, most long tide gauge records demonstrate a slow acceleration in MSL between the 19th and 20th centuries of the order of approximately 1 mm/year per century, 12,83,84 findings which are supported by evidence from proxy (i.e., salt marsh) data, as discussed in Section “SEA LEVEL AND GEODESY.” 85,86 However, the significance of that acceleration (in the tide gauge data at least) depends on the analysis method, some analyses finding that the evidence for acceleration is less persuasive than others 87–89 . (See discussion of methods for determining acceleration in Refs.…”
Section: Twentieth‐twenty First Century Msl Rise and Accelerationmentioning
confidence: 99%
“…In the past, several studies investigated the presence of a global acceleration of sea-level rise with mixed results (see, e.g., Woodworth, 1990, Douglas, 1992, Church and White, 2006, Holgate, 2007, Merrifield et al, 2009, Woodworth et al, 2009, Houston and Dean, 2011, Jevrejeva et al, 2013, Kopp, 2013, Hogarth, 2014, Watson, 2016a.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Watson (2016a) analyzed five tide gauge stations and concluded that "there is now more robust, convincing evidence of recent acceleration in the trend of global mean sea level". But then, Watson (2016b) study reverted and concluded that there is no consistent or statistically significant evidence that recent rates of rise are higher or abnormal in the context of the historical records available for the United States.…”
Section: Introductionmentioning
confidence: 99%
“…With SSA applied to the analysis of tide gauge records and satellite altimetry time series, finer scales of periodic and quasiperiodic modes are identified (Haddad et al, 2013;Jevrejeva et al, 2006;Unal & Ghil, 1995). Trends of different global mean sea level reconstructions are estimated by SSA and compared to show more robust, convincing evidence of recent acceleration (Watson, 2016b). Based on simulated data tests, along with the maximal overlap discrete wavelet transform (MODWT) method, SSA is proven to be one of the two most recommended tools for sea level research (Watson, 2016a).…”
mentioning
confidence: 99%